1967
DOI: 10.1002/1097-0142(196709)20:9<1452::aid-cncr2820200912>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation disorders in cancer.I. Clinical and laboratory studies

Abstract: A comprehensive study of the hemostatic and coagulation mechanisms in 50 patients with disseminated malignancy was carried out. Significant laboratory abnormalities were found in the majority of patients. The most common pattern was the “hypercoagulable state.” This included short bleeding time, decreased silicone coagulation time and partial thromboplastin time, increased tolerance to heparin, marked elevation of plasma levels of factors I, II, V, VIII, IX and XI and acceleration of thromboplastin generation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

1969
1969
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(63 citation statements)
references
References 35 publications
0
61
0
2
Order By: Relevance
“…In some types of carcinoma, especially carcinoma of the pancreas, the incidence is very high. Different histological types of pancreatic carcinoma h.owever, are associated with pronounced differences in the incidence of multiple thrombi (Lafler and Hinerman, 1961 has been suggested that the same abnormalities which lead to an increased incidence of thrombosis in other types of disseminated malignant disease might be present in myelomatosis also (Miller et al, 1967). Sanchez-Avalos et al (1969) suggested that the release of small amounts of thromboplastic material by the tumour cells may result in accelerated consumption of some coagulation factors and, in consequence, a compensatory overproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some types of carcinoma, especially carcinoma of the pancreas, the incidence is very high. Different histological types of pancreatic carcinoma h.owever, are associated with pronounced differences in the incidence of multiple thrombi (Lafler and Hinerman, 1961 has been suggested that the same abnormalities which lead to an increased incidence of thrombosis in other types of disseminated malignant disease might be present in myelomatosis also (Miller et al, 1967). Sanchez-Avalos et al (1969) suggested that the release of small amounts of thromboplastic material by the tumour cells may result in accelerated consumption of some coagulation factors and, in consequence, a compensatory overproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant diseases, especially carcinoma, predispose to thrombosis (Lieberman et al, 1961;Miller et al, 1967;Wiernik and Serpick, 1969). In some types of carcinoma, especially carcinoma of the pancreas, the incidence is very high.…”
Section: Discussionmentioning
confidence: 99%
“…Укорочение времени сверты-вания наблюдается редко и часто объясняется ошиб-ками на преаналитическом этапе (который в целом имеет большое значение в диагностике гиперкоагуля-ции, так как очень легко вызвать гиперкоагуляцию недостаточно аккуратным обращением с цельной кро-вью). Хотя в единичных работах 1970-90-х годов встречается упоминание об укорочении ПВ в состоя-ниях с повышенным риском тромбоза [4,5], в насто-ящее время применение ПВ (в стандартизированном варианте -МНО) в отношении к тромбозу обычно ограничивается оценкой эффективности дозы антаго-нистов витамина К [6].…”
Section: O N C O G E M a T O L O G Y 3 ' 2 0 1 5 V O L 10unclassified
“…In cancer patients, platelet activation and thromboembolic events frequently occur [1][2][3]. Thrombocytosis is also observed in patients with cancer including colorectal cancer and elevated platelet count is associated with poor survival [4][5][6].…”
Section: Introductionmentioning
confidence: 99%